Peran Auditor Internal Dalam Pendanaan Dukungan Operasi Sekolah (Bos) - Heka Herawati; Adinda Maudia Savira; Kiki Adilianti (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The aim of this research is to identify and explain the role of internal audit in the allocation of BOS funds. This research uses a qualitative approach with library or library research. Audit is an operational process carried out by a qualified and independent auditor, whose aim is to ensure compliance with the conditions relating to the operation of an economic entity and its standards. Auditors carry out examinations by collecting and presenting evidence systematically, analytically, critically and accurately to provide opinions or conclusions and recommendations to stakeholders. BOS Fund Management Audits are carried out in accordance with the provisions of the audit standards of the Ministry of State Apparatus Empowerment (PER/05/M.PAN-03/2008 APIP-AUDIT-STANDARDS). Several requirements must be met before an audit can be performed.(Comparative et al., 2023). This research aims to understand the accounting information system for cash receipts and cash disbursements in school operational assistance funds (BOS). The variables used in this research are Accounting Information Systems, Cash Receipts and Cash Disbursements. The method used in this research is a qualitative method by utilizing data collection techniques then carrying out observations, interviews, documentation, triangulation and literature study. The data used in this research is primary data using observations and interviews with the Nurul Ikhwan Selabintana Sukabumi Islamic Vocational School.(Asep & Wr, 2021)